Seasonal Variations in Triptan Prescription in Japan: A Nationwide Time‐Series Analysis - Muneto Tatsumoto; Koichi Hirata; Takeo Nakayama; Kentaro Yamato; Hiromi Sano; Lyo Inuyama (Brain and Behavior)
ABSTRACT Objective This study aimed to investigate seasonal differences in migraine onset in Japan and associated trends in the prescription of triptan. Background The relationship between seasonal changes and the onset of migraine remains largely unknown. Methods We combined the large‐scale medical claims data in Japan with city‐level meteorological data presented by the Japan Weather Association. The study period was from January 2018 to December 2019. We included patients aged 18–74 years and diagnosed with migraine who had been prescribed triptans in 2018. Patients were categorized into four groups according to the seasons when they were prescribed medicines: winter (January–March), spring (April–June), summer (July–September), and autumn (October–December). Migraine onsets were defined by the time of triptan prescription. The least‐square mean differences between the seasons were estimated with linear mixed‐effects models for repeated measures, adjusting for the following covariates: sex, age, acute migraine medications, and medications for migraine prevention, comorbidities that can induce migraine, other comorbidities, and the estimated age of menopause in females. Results We analyzed data of 12,986 patients in 2019 after triptan had been prescribed (female 74.1%). The mean age was 44.1 years. The mean number of amounts of prescriptions comprised 2.12 tablets/month in spring and summer, whereas there were only 2.09 tablets/month in autumn and 2.00 tablets/month in winter. The amount of triptan prescribed in winter was lower than in spring (β = −0.117; 95% confidence interval [CI]: −0.169 to −0.065). Conclusion The study results suggest that seasons can have an impact on the onset of migraine; thus, clinicians may advise patients to take preventive actions, including self‐care and drug therapies, from the winter stage. This should be done in order to reduce the number of migraine onsets in high‐risk season (spring) regardless of region.